WORLD ENGLISHES FROM A HOLISTIC VIEW AND CONSIDERATIONS ON ENGLISH EDUCATION IN VIETNAM - Hao, Tran Thi; Phuong, Ngo Dinh (VNU Journal of Foreign Studies, 2017)
The development of English as the mutual language among ASEAN since 2008 and the formation of ASEAN Economic Community since 2015 have set milestones in the social and educational development of each country in this organisation. In English education in Vietnam, understanding the diversity of Englishes in the organisation has become an important task. This article aims to present a holistic view of World Englishes (WE) in research generally and in relation to English education in Vietnam particularly by illustrating the Vietnamese English teachers’ perceptions of WE in the Vietnamese teaching context. The data were collected via an online questionnaire using a snowball sampling method from seventy-six respondents who are English lecturers from twenty-six universities or colleges in Vietnam. The data were also collected from focus group interviews with fve participants who were doing Master Degree in Applied Linguistics at an Australian university. The article delineates the fndings of the Vietnamese English teachers’ perceptions towards WE and their experiences in introducing WE in their teaching context. Discussion of English education in Vietnam, including issues in English teaching, English teachers’ development and considerations of the policy context, is also be presented.